Numerical Methods Applied to the Kinematic Analysis of Planar Mechanisms and Biomechanisms - Rosa, H. N. [UNESP]; Bazani, M. A. [UNESP]; Chavarette, F. R. [UNESP] (Springer Nature, 2022)
This article presents a numerical methodology for the kinematic analysis of planar mechanisms based on the closed loop method. Initially, the mesh is defined with the aid of complex notation and, through iterative processes, the configuration of the mechanism is defined as a function of time. For the calculation of speeds and accelerations, the 4th order numerical derivative was applied. After applying the procedure, satisfactory results were obtained for a certain step size range, showing itself as a useful tool for kinematic analysis.
Keywords: Closed loop; Kinematics; Mechanisms; Numerical derivation; Numerical methods